IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) DALAM MELATIH BERFIKIR KRITIS SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 2 BUKITTINGGI - Adetiya Farah Oktavia; Muhiddinur Kamal; Syafrizal Syafrizal (ADIBA : JOURNAL OF EDUCATION, 2024)
This research is motivated by current students, especially at the high school level, where there are still students who are passive and have not been able to develop critical thinking in the learning process. If they are not trained starting from now, it will be difficult in the future when they grow up and are involved. in the world of work. So, many parents are now taking their children to do additional study outside of school to broaden their children's insight and abilities and hone their children's abilities more deeply. However, all learning activities in class are still said to be less than optimal, especially in terms of maximizing learning time which is less effective. The aim of this research is to determine the level of students' critical thinking abilities in learning using the Teams Games Tournament (TGT) model, as well as to determine the factors that inhibit and support learning using the Teams Games Tournament (TGT) learning model. The type of research used is qualitative research. Data collection techniques use observation. Meanwhile, the data analysis technique used is descriptive interpretative. The results of the research show that the Teams Games Tournament (TGT) learning model really helps students understand the learning material. One of the things that supports learning using the Teams Games Tournament (TGT) model is the supporting media used, while the inhibiting factor in learning using the Teams Games Tournament (TGT) model is the lack of time in carrying out the learning process.